(untitled) (Journal of Comparative Social Work, 2014)
Good quality assessment in Child Protection is crucial to ensure adequate protection and provision. This article explores social workers` experiences with two different Child Protection assessment models: the “professional judgment model”, exemplified by Norway, and the “structured assessment model”, exemplified by England. The aim is to explore the experiences of social workers who carry out assessments in England and Norway, and compare and discuss these experiences in light of “accountability” theory.